KAJIAN PRAKTEK CARA MENJUAL DALAM BISNIS RITEL DAN STRATEGI PENGAWASANNYA - Heny Sukesi (Buletin Ilmiah Litbang Perdagangan, 2010)
Nowadays, retail business in Indonesia shows a rapid development. This condition drives the retail businessmen to undertake various ways to grab the market by conducting selling practices such as giving discount, prize, voucher and promotion..Current selling practices display an indication of deceit and trickery towards consumers. On the other hand, monitoring efforts for consumer protection have not been optimal. This is due to the lack of regulation and technical guidance monitoring handbook. The aim of this article is to know the condition and selling practices in retail business as well as to formulate a monitoring strategy. Juridical normative.Sociological method are use to analyze selling practice and the problems of business retail. The results shows that several countries are more advanced and established in monitoring selling practices and selling practices in Indonesia use many deceitful selling practices.A detailed technical and operational guideline is required to regulate selling practices of retail business.